Assessment Of Knowledge and Performance of Ayush Doctors Posted in Collocation Under National Rural Health Mission in Udaipur Division, Rajasthan - Kumar, Arun; Keerti; Sharma, Chandra Prakash; Sharma, Sandeep; Garg, Kapil; Jain, Rohit (National Journal of Community Medicine, 2013)
Background: The objective of mainstreaming of AYUSH through co-location at PHCs (Primary Health Centres) and CHCs (Community Health Centres) meant to strengthen the existing health facilities functionally and correct the architectural flaw in the public health care delivery system and also to bring AYUSH stream side by side with dominant stream that is allopathy. Objective: Purpose is to assess the knowledge and performance of AYUSH practitioners posted in collocation with allopathic counterparts. Material and Methods: .All 67 AYUSH doctors posted at different Primary health centres /Community health centres/District hospitals with collocation in randomly selected three districts of Udaipur division were included in the study.Data were analysed statistically by applying analysis of variance using Epi Info Ver 6.0 r Results: Mean age of the AYUSH doctors found to be 35±3.2 years. Majority 49(73.1%) of AYUSH doctors posted in collocation were from ayurveda stream. Majority 58(86.5%) of AYUSH doctors were found to be trained on SBA (Skill Birth Attendant). Maximum respondents i.e 28(41.8%) had good knowledge followed closely by 27(40.3%) doctors with average knowledge. 10(15%) of the respondents had poor knowledge. Cent percent involvement of AYUSH doctors were observed in majority of health care services except management of neonatal and childhood illness.